Reactivation of associative structure specific outcome responses during prospective evaluation in reward-based choices - Maya Zhe Wang (Nature Portfolio, 2017)
How the brain evaluates options to make a reward-based choice is unclear. Here, authors show that, prior to choice, neural activity patterns to the potential outcomes are reactivated in macaque orbitofrontal cortex, in a way that reflects the unique event sequences leading up to the outcomes.